2020
DOI: 10.18639/merj.2020.9900005
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Investments in the Chinese Bond Markets

Abstract: The Chinese bond market is the second largest in the world. However, studies on Chinese bond markets are very few, and especially there are no studies on foreign investments in the Chinese bond markets. This study fills the gap in the academic literature by focusing on foreign investments in the Chinese bond markets. By using the least-squares model with breaks, this study finds that although, in theory, the factors of exchange rate, yield spread, and yield correlation should play a significant role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Chinese bond markets have not been studied extensively. Liu (2020Liu ( , 2022 conducted a review on this topic; other research has targeted Chinese bond yields (Porter, Cassola, 2011), the microstructure of Chinese government bonds (Bai, Fleming, Horan, 2013), local government debt (Ang, Bai, Zhou, 2015), government bond yields (Loechel, Packham, Walisch, 2016), the corporate bond market (Luo, Ye, Hu, 2016;Liu et al, 2019;Ding, Xiong, Zhang, 2020), the green bond (Deng et al, 2020), and bond portfolio management (Fan, Jiang, Zhou, 2015).…”
Section: Foreign Investments In Chinese Government Bond Marketsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chinese bond markets have not been studied extensively. Liu (2020Liu ( , 2022 conducted a review on this topic; other research has targeted Chinese bond yields (Porter, Cassola, 2011), the microstructure of Chinese government bonds (Bai, Fleming, Horan, 2013), local government debt (Ang, Bai, Zhou, 2015), government bond yields (Loechel, Packham, Walisch, 2016), the corporate bond market (Luo, Ye, Hu, 2016;Liu et al, 2019;Ding, Xiong, Zhang, 2020), the green bond (Deng et al, 2020), and bond portfolio management (Fan, Jiang, Zhou, 2015).…”
Section: Foreign Investments In Chinese Government Bond Marketsmentioning
confidence: 99%
“…The change in market efficiency was likely due to the increase in foreign investment, which helped form a more diverse investor base for Chinese government bonds and, as a result, improved liquidity and brought more diverse trading strategies. Liu (2020) analyzed the development of China's government bond markets from 2015 to 2019, concluding that the major game-changing policy initiative was opening up to foreign investors.…”
Section: Foreign Investments In Chinese Government Bond Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Responding to the increasing accessibility to China’s bond market for foreign investors as a result of these further opening-up measures, on March 1, 2017 Bloomberg Barclays Benchmark Fixed Income Index family launched new indices to cover Chinese bonds denominated in RMB ( Bloomberg News , 2017). The other two major global bond indices including FTSE Russell World Government Bond Index, and JP Morgan, EM Global Diversified have also included some Chinese onshore bonds (Liu, 2020b). It is part of the Chinese government’s policy of further opening up its domestic markets (Liu, 2020c).…”
Section: Chinese Bond Markets Government Bond Markets and Foreign Inv...mentioning
confidence: 99%
“…This figure has increased from 2% in June 2014 to 8.5% in December 2019 and has become comparable to other Asian economies. Liu (2020b) especially examined the determinants of foreign investments in the Chinese government bond market, and found that foreign investors' trading strategies have been evolving. For example, initially the main foreign investors were central banks and similar institutions, and they primarily considered strategic factors rather than pure return or risk factors during June 2014 to July 2016.…”
Section: Efficiency Tests On Chinese Government Bond Marketsmentioning
confidence: 99%